Effect of structure and composition of cationic liposomes on the delivery of siRNA in vitro and in vivo - Gladkikh, Daniil V.; Shmendel, Elena V.; Makarova, Darya M.; Maslov, Mikhail A.; Zenkova, Marina A.; Chernolovskaya, Elena L. (Frontiers in Pharmacology, 2025)
This study explores the effects of the modifications of siRNA delivery systems based on cationic liposomes containing the polycationic amphiphile 2 × 3 and lipid-helper DOPE on their ability to deliver therapeutic siRNA in vitro and in vivo. We supplied the core liposome system with lipoconjugates differing in PEG length weights and conjugate structure, and additionally modified with a folate residue as an addressing moiety. The in vitro data revealed no direct correlations between PEG length, lipoconjugate structure and the transfection efficiency of siRNA lipoplexes. In vivo biodistribution studies highlighted the significant influence of tumor presence on siRNA accumulation and biodistribution, underscoring the importance of adaptive delivery systems. In healthy mice, the largest amount of siRNA accumulates in the liver, whereas in tumor-bearing mice, accumulation in the kidneys increases, with a noticeable amount of siRNA accumulating in the tumor. Despite the longer linear PEG increasing the circulation time of siRNA, diP800 showed the best tumor accumulation. Anti-TTR siRNA complexes with all liposomal formulations demonstrated significant suppression of the Ttr mRNA in the liver, complexes with diP2000 and 2 × 3 liposomes demonstrated the highest silencing efficiency. These results contribute to advancing nucleic acid therapeutics by offering a comprehensive understanding of liposomal delivery system optimization.